Recurrence of Herpetic Keratitis after COVID-19 Vaccination: A Report of Two Cases - Ali Mahdavi Fard; Jeffrey Desilets; Sangita Patel (Case Reports in Ophthalmological Medicine)
Background. Recurrence of herpetic keratitis following vaccination has been documented following vaccination with the Zostavax, trivalent flu, hepatitis A, and rabies vaccines. The USFDA and WHO have acknowledged that the novel COVID-19 vaccines similarly have a risk of reactive immunologic-based inflammation, namely, myositis, pericarditis, and Guillain-Barré syndrome. Case Presentation. We present two patients with latent herpetic keratitis who experienced reactivation of keratitis within weeks of COVID-19 vaccination despite prolonged periods of prior latency. A 52-year-old healthy male with no herpes simplex virus (HSV) keratitis recurrences in two years developed visual decline and patchy stromal haze within 24-48 hours of receiving the second Pfizer-BioNTech (COVID-19 BNT162b2) vaccine. A 67-year-old female with chronic neurotrophic keratitis developed her most severe exacerbation of herpes zoster keratitis in over 10 years occurring 2-3 weeks after her first Moderna (mRNA-1273) vaccine, which was later complicated by bacterial superinfection. Conclusions. The COVID-19 vaccines work by generating both adaptive humoral and cellular immune responses in humans, including elevation of anti-spike neutralizing antibody titers, antigen-specific CD4+ and CD8+ T-cell responses, and increased levels of proinflammatory cytokines such as interferon gamma (IFNγ). The general activation of the T-cell-mediated immune response and proinflammatory cytokines such as IFNγ may underlie the role of the COVID vaccines in reactivation of herpetic stromal keratitis and the clinical findings in our reported cases.